Tinjauan Filsafat Hukum Islam terhadap Pelaksanaan Remisi bagi Pelaku Tindak Pidana - Rahman, Inayatur (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The paper aims to examine the perspective of Islamic legal philosophy on the implementation of Remission in terms of legal principles and justice. There are three conclusions from this article. Firstly, good behavior which is a requirement for a criminal to receive remission cannot be named as the concept of repentance in Islamic law. Secondly, the remission given to the perpetrator is not based on the principles of law and justice in Islam. Thirdly, it is suggested that Presidential Decree No. 174 of 1999 concerning Remission needs to be reviewed by distinguishing the types of crimes committed, so that justice, peace, and benefit for the community can be obtained. Even so, it should be noted that based on the philosophy of Islamic law, remission which is given to the criminals (convicts or child criminals) who have committed serious human rights crimes, corruption, drug dealers, murder, and transnational crimes, etc. is not following the principles of law, justice and benefit.